Open carpal tunnel release and diabetes: a retrospective study using PROMs and national quality registries - Katarina Eeg-Olofsson; Malin Zimmerman; Mikael Åström; Marianne Arner; Lars Dahlin (BMJ Open)
Objectives To study patient-reported outcome after open carpal tunnel release (OCTR) for carpal tunnel syndrome (CTS) in patients with or without diabetes using national healthcare quality registries.Design Retrospective cohort study.Setting Data from the Swedish National Quality Registry for Hand Surgery (HAKIR; www.hakir.se) were linked to data from the Swedish National Diabetes Register (NDR; www.ndr.nu).Participants We identified 9049 patients (10 770 hands) operated for CTS during the inclusion period (2010–2016).Primary outcome measures Patient-reported outcome measures were analysed before surgery and at 3 and 12 months postoperatively using the QuickDASH as well as the HAKIR questionnaire with eight questions on hand symptoms and disability.Results Patients with diabetes (n=1508; 14%) scored higher in the QuickDASH both preoperatively and postoperatively than patients without diabetes, but the total score change between preoperative and postoperative QuickDASH was equal between patients with and without diabetes. The results did not differ between patients with type 1 or type 2 diabetes. Patients with diabetic retinopathy scored higher in QuickDASH at 3 months postoperatively than patients with diabetes without retinopathy. In the regression analysis, diabetes was associated with more residual symptoms at 3 and 12 months postoperatively.Conclusions Patients with diabetes experience more symptoms both before and after OCTR, but can expect the same relative improvement from surgery as patients without diabetes . Patients with retinopathy, as a proxy for neuropathy, may need longer time for symptoms to resolve after OCTR. Smoking, older age, higher HbA1c levels and receiving a diabetes diagnosis after surgery were associated with more residual symptoms following OCTR.